Ahmad Tohari, El regreso de Karman, traducción e introducción de Evi Yuliana Siregar y Fernando Octavio Hernández, México, El Colegio de México, 2015, 158 pp. - Luna Mariscal, Karla Xiomara (Estudios de Asia y África, 2016)
Ahmad Tohari, El regreso de Karman, traducción e introducción de Evi Yuliana Siregar y Fernando Octavio Hernández, México, El Colegio de México, 2015, 158 pp.